(untitled) (African Journal of Biomedical Research, 2021)
To determine the prevalence of Vitamin D deficiency and insufficiency across trimesters of pregnancy. A cross-sectional study involving 160 women (40 in each trimester of pregnancy making a total 120 and 40 non-pregnant controls) was conducted at the University of Maiduguri Teaching Hospital, Maiduguri from 1st January 2018 to 31st December 2018. The subjects of the study were randomly recruited at the booking clinic. Socio-demographic characteristics, staple food and gestational age were obtained. Blood sample was collected for 1,25(OH)2 D3, total protein and albumin. The data was analyzed using the Minitab statistical software version 12.21 (Minitab Inc, Pennsylvania, USA). The Mean±SD age of the patients studied was 28.2±4.1 year and 114 (71.3%) were city dweller. There were no statistically significant differences in the parity, BMI, total protein and albumin in both the subjects and controls. On the other hand, the Mean±SD Vitamin D level was lower (23.11±4.27Miu) among the pregnant women compared to 34.78±2.96 Miu in the non-pregnant (F=17.40, P=0.00). Vitamin D deficiency was 52.5% in the first trimester, increased to 55.0% in the second trimester and dropped to 22.5% in the third trimester. While, vitamin D insufficiency roused from 40.0% in the first trimester to 60.0% in the third trimester. There is high prevalence of Vitamin D deficiency and insufficiency among pregnant women in Maiduguri. There is need to provide vitamin D supplementation preconception or early in the antenatal period so that the women will achieve Vitamin D sufficiency in pregnancy and beyond